Absorbable barbed suture device for laparoscopic peritoneal closure after hernia repair via the transabdominal preperitoneal approach: A single‐center experience with 257 cases. Issue 2 (11th July 2018) - Chihara, Naoto; Suzuki, Hideyuki; Sukegawa, Makoto; Watanabe, Masanori; Oyama, Rina; Shimizu, Takao; Uchida, Eiji
Abstract: Introduction: The laparoscopic transabdominal preperitoneal approach requires peritoneal closure and technically skilled knotting. We have started to use a barbed running suturing device (V‐Loc 180) without knotting for transabdominal preperitoneal repair of hernias. This study aimed to determine whether using V‐Loc 180 was safe and shortened the time for laparoscopic peritoneal closure. Methods: Between December 2010 and February 2017, 3‐0 V‐Loc 180 and a multifilament absorbable running suture (3‐0 Vicryl) were used for three‐port transabdominal preperitoneal repair of inguinal hernia in 363 cases. Data including peritoneal closure time and the complications were retrospectively recorded. Results: Factors identified as significantly prolonging the peritoneal closure time were the hernia side ( P = 0.0269), the type of hernia ( P = 0.001), the suture device used ( P < 0.0001), and the surgeon's experience ( P < 0.0001). Use of the barbed suture was associated with a significantly shorter peritoneal closure time than the multifilament suture (mean closure time: 10.2 and 12.7 min, respectively). While there were no postoperative complications in the barbed suture group, there were two cases (1.9%) of postoperative complications in the multifilament suture group ( P = 0.0272). Conclusion: We demonstrated that the use of the barbed suturing device for laparoscopic peritoneal closure was safe and feasible.